The Association of Low Taurine Levels with Diabetic Neuropathy in Iraqi Patients - Rand Thair Abdulkader; Nada A. Kadhim; Firas Younus Muhsin (Indian Journal of Forensic Medicine & Toxicology, 2022)
Aim of this Study: this study has been carried out to evaluate the role of taurine, and lipid profile inprogression of diabetic complication.Methods: this work included 81 Iraqi people (age ranged 40-65). Healthy control subjects (G1group=28), type 2 diabetes mellitus without any complications (G2 group=26), and type 2 diabetesmellitus with peripheral neuropathy (DPN) (G3 group=27). Diagnosis of the disease was based onseveral symptoms and questions under the supervision of the consultant supervisor at the center. Serumtaurine, lipid profile (Cholesterol, triglycerides, HDL, LDL, and VLDL) besides fasting blood glucoseand plasma HbA1c were determined for each participant. Results: The results of taurine revealed thatthere was a highly significant decrease in G2 and G3, as compared to G1. The mean values of serumcholesterol showed no significant difference between G2 and G3 as compared with G1while serumtriglycerides (TG), LDL and VLDL showed a high significant increase in G2 and G3 as comparedto G1. The results of serum HDL levels showed that there was a high significant decrease in G2 andG3 as compared to G1. No significant differences were found in body mass indices in all the studiedgroups while WC, HC, WHR, and WHtR showed high significant increase in G2and G3 as comparedto G1. Systolic blood pressure significantly increased in G2 and G3 while diastolic blood pressuresignificantly increased in G3 only.Conclusion: Serum taurine levels were decreased in patients with T2DM and DPN .The reducing intaurine synthesis was not related to FBG, HbA1c, and dyslipidemia. We also found that taurine levelsmay be more important in the development of diabetes complications.